Alkali-treated graphitized carbon loaded platinum-based metal catalyst and preparation method thereof
By alkali treatment of graphitized carbon to increase its defect position and specific surface area, the problem of poor stability of existing fuel cell cathode catalysts is solved, and an alkali-treated graphitized carbon-supported platinum-based metal catalyst with high electrochemical activity and stability is prepared.
Patent Information
- Application Number
- CN202510089773.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
AI Technical Summary
The existing fuel cell cathode catalysts have high cost and poor stability, especially under high oxygen concentration, high moisture content and high temperature conditions, the insufficient degree of graphitization of the carbon support leads to poor electrochemical stability of the catalyst.
By alkali treatment of graphitized carbon, its defect position and specific surface area are increased, thereby improving the dispersion and stability of platinum or platinum alloy particles, an alkali-treated graphitized carbon-supported platinum-based metal catalyst with high electrochemically active area and mass specific activity is prepared.
It significantly improves the stability and performance of the catalyst, is better than commercial platinum carbon catalysts, and can maintain high catalytic activity and durability under high temperature and high oxygen conditions.
Smart Images

Figure CN119833661A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of fuel cell catalysts, and mainly to an alkali-treated graphitized carbon-supported platinum-based metal catalyst and a preparation method thereof. Background Art
[0002] Fuel cells have achieved rapid development in recent years due to their high energy efficiency and environmental friendliness. However, the high cost and poor stability of their cathode catalysts are the main reasons that restrict the large-scale commercialization of fuel cells. The most advanced catalysts are based on Pt and Pt-based alloy nanomaterials dispersed on high-surface-area carriers, where the role of the carrier is to stabilize the nanoparticles to improve the atomic utilization of the catalyst and provide effective electronic conductivity.
[0003] At present, a variety of conductive materials have been developed as carriers of platinum, including nanostructured carbon, conductive diamond, conductive oxides and carbides. Among them, nanostructured carbon materials are the most successful due to their high surface area, high conductivity, good interaction with platinum and reasonable stability in acidic media. At present, commercial carbon materials such as XC72, Ketjenblack, BP2000, etc. have been used in Pt / C catalysts. However, as amorphous carbon materials with a low degree of graphitization, they are affected by high oxygen concentration, high water content, low pH, high temperature up to 100°C and high electrode potential in proton exchange membrane fuel cells, and severe carbon corrosion has been observed. Its electrochemical stability still needs to be improved.
[0004] To address this major challenge, a variety of carbon supports have been studied and found that factors such as their graphitization degree, morphology, and surface area have a significant impact on catalytic activity and durability.
[0005] Due to the multiple degradation mechanisms of low platinum loading catalysts, their durability is still insufficient for practical applications. The poor loading stability leads to the shedding of Pt nanoparticles, particle agglomeration, compaction and electrode porosity loss, which is a key factor limiting the durability of current catalysts. Generally, the surface defects, pore structure and specific surface area of graphitized carbon materials are greatly reduced due to the rearrangement of carbon atoms at high temperatures, which affects the dispersion of metal particle catalysts on the surface. Carbon nanotubes with high graphitization degree have attracted much attention in recent years. It has been found that the stability of catalysts supported by such new carbon nanostructured materials is enhanced. Carbon nanotubes are generally considered to be rolled graphene sheets with coaxial and fewer dangling bonds and defects than carbon black. Oxidizing atoms / groups have difficulty attacking the closed structure of CNTs, so they are relatively stable under strong oxidizing conditions. However, in the platinum cathode supported by carbon nanotubes, the Nafion ionomer has poor dispersion and limited electrochemical active area, resulting in poor performance of fuel cell membrane electrode. The high cost of preparing carbon nanotubes also limits its commercial application. It can be seen that metal nanoparticles loaded with more defect sites on the surface while having a high degree of graphitization to ensure high stability are ideal carbon support materials in fuel cell catalysts. Therefore, it is necessary to propose a preparation method to obtain carbon support materials with ideal performance. Therefore, the existing technology still needs to be improved and developed. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide an alkali-treated graphitized carbon-loaded platinum-based metal catalyst and a preparation method thereof, aiming to solve the problem that most existing graphitization methods make it difficult to evenly disperse platinum nanoparticles on the graphitized carrier.
[0007] The technical solution of this application is as follows: In a first aspect, the present application provides a method for preparing an alkali-treated graphitized carbon-supported platinum-based metal catalyst, which comprises the following steps: Dispersing graphitized carbon in an alkali treatment solution and soaking it to obtain a mixture; The mixture is dried, heat treated in an argon atmosphere, and washed to obtain alkali-treated graphitized carbon; The alkali-treated graphitized carbon is impregnated with a platinum-based metal catalyst to obtain the alkali-treated graphitized carbon-supported platinum-based metal catalyst.
[0008] The present application performs alkali treatment on graphitized carbon to obtain alkali-treated graphitized carbon with relatively abundant defects, which can be used as a platinum-based catalyst carrier for hydrogen fuel cells. Platinum or platinum alloy particles are well dispersed on the alkali-treated graphitized carbon carrier, which solves the problems of weak interaction between platinum and graphitized carbon and difficulty in uniformly loading platinum particles on graphitized carbon, and has a high electrochemical active area and mass specific activity; and the alkali-treated graphitized carbon still has a highly graphitized structure, and the loaded platinum-carbon catalyst particles are moderate, so the catalyst has excellent stability, which is significantly better than commercial platinum-carbon catalysts.
[0009] Furthermore, the alkaline treatment solution is a mixed solution of alkaline solution and anhydrous ethanol; The concentration of the alkaline solution is 0.5-10 mol / L, and the alkali in the alkaline solution is one of calcium hydroxide, magnesium hydroxide, rubidium hydroxide, cesium hydroxide, lithium hydroxide, and potassium hydroxide.
[0010] Furthermore, the alkali in the alkaline solution is potassium hydroxide.
[0011] Furthermore, the heat treatment temperature in the argon atmosphere is 200-1800° C., and the treatment time is 0.1 h-10 h.
[0012] Further, the ratio of the graphitized carbon to the alkaline treatment liquid is 1:1-1000 (g / ml); The volume ratio of the alkaline solution to anhydrous ethanol is not higher than 50:1.
[0013] Furthermore, the preparation steps of the graphitized carbon include: The amorphous carbon material is kept at 1200-3000°C for 75 minutes and then naturally cooled to room temperature.
[0014] Furthermore, the amorphous carbon material is one or more of Vulcan XC72, KB300, KB600, BP2000, and Toray carbon.
[0015] Furthermore, the step of impregnating the alkali-treated graphitized carbon with a platinum-based metal catalyst comprises: The alkali-treated graphitized carbon, the precursor solution and water are stirred and mixed, and treated in a reducing atmosphere at 200-1000° C. for 0.1-10 h; The precursor solution is a platinum precursor solution, or the precursor solution includes a platinum precursor solution and a transition metal precursor solution.
[0016] Furthermore, the reducing atmosphere is an argon-hydrogen atmosphere, and the volume proportion of hydrogen is 1-50%; The platinum precursor in the platinum precursor solution is one or more of H2PtCl6∙6H2O, K2PtCl6, Na2PtCl6, Na2PtCl4, K2PtCl4, Pt(NH3)4Cl2, Pt(NH3)2(NO2)2, and Pt(NO3)2; The transition metal precursor in the transition metal precursor solution is one or more of chloroauric acid, cobalt chloride, cobalt nitrate hexahydrate, cobalt sulfate, cobalt acetate, nickel nitrate, ferric chloride, and ferric nitrate.
[0017] In a second aspect, the present application also provides an alkali-treated graphitized carbon-supported platinum-based metal catalyst, wherein the catalyst is prepared by the preparation method of the alkali-treated graphitized carbon-supported platinum-based metal catalyst as described in the first aspect.
[0018] Beneficial effects: The present application proposes to modify the surface of a carbon carrier with a high degree of graphitization, thereby greatly increasing the defect sites and specific surface area of the material while maintaining the graphitized structure, effectively dispersing the platinum or platinum alloy catalyst, and effectively enhancing the dispersion of the Nafion ionomer, so that the catalyst has a higher mass specific activity and durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a comparison chart of the ORR performance of the alkali-treated graphitized carbon-supported platinum catalyst of Example 1 of the present application and the graphitized carbon-supported platinum catalyst of Comparative Example 1.
[0020] Figure 2 This is a graph showing the ORR results of the alkali-treated graphitized carbon-supported platinum catalyst in Example 1 of the present application at each stage of the 30,000-cycle stability test.
[0021] Figure 3 This is a comparison chart of MA at various stages of the 30,000-cycle stability test of the alkali-treated graphitized carbon-supported platinum catalyst of Example 1 of the present application.
[0022] Figure 4 This is an XRD comparison diagram of the alkali-treated graphitized carbon of Example 2 of the present application and the graphitized carbon of Comparative Example 2.
[0023] Figure 5 3 is a TEM comparison diagram of the graphitized carbon-supported platinum catalyst (a) of Comparative Example 2 of the present application and the alkali-treated graphitized carbon-supported platinum catalyst (b) of Example 2.
[0024] Figure 6 This is a comparison chart of the ORR performance of the alkali-treated graphitized carbon-supported platinum catalyst of Example 2 of the present application and the graphitized carbon-supported platinum catalyst of Comparative Example 2.
[0025] Figure 7This is a graph showing the ORR results of the alkali-treated graphitized carbon-supported platinum catalyst in Example 2 of the present application at each stage of the 100,000 cycle stability test.
[0026] Figure 8 This is a comparison chart of MA at various stages of the 100,000 cycle stability test of the alkali-treated graphitized carbon-supported platinum catalyst of Example 2 of the present application.
[0027] Fig. 9 This is a TEM comparison diagram of the alkali-treated graphitized carbon-supported platinum catalyst before and after the stability test of Example 2 of the present application, (a) is before the stability test, and (b) is after the stability test.
[0028] Fig.10 This is the ORR performance diagram of the alkali-treated graphitized carbon-supported platinum-cobalt catalyst of Example 5 of the present application. DETAILED DESCRIPTION
[0029] The present application provides an alkali-treated graphitized carbon-supported platinum-based metal catalyst and a preparation method thereof. To make the purpose, technical solution and effect of the present application clearer and more specific, the present application is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0030] The common preparation method of graphitized carbon is carried out at high temperature, and carbon is rearranged at high temperature to form a graphite structure with a smooth surface and no defects. On the carbon carrier with a graphitized structure without defects, the metal nanoparticles have no sites for interaction with carbon, resulting in the inability to effectively disperse the nuclei of the metal nanoparticles during deposition, and they are easy to agglomerate to make the particles grow. The metal nanoparticles are severely agglomerated, and the particle distribution is uneven, ranging in size from a few nanometers to 200 nanometers. The surface atomic utilization rate of the formed catalyst is low and the activity is reduced; because the carbon carrier has no or fewer defects, it will also cause a small number of metal nanoparticles deposited on the surface of the graphitized carbon to fall off in the solution during the subsequent oxygen reduction reaction and lose their activity.
[0031] To address this problem, the present application provides a method for preparing an alkali-treated graphitized carbon-supported platinum-based metal catalyst, specifically, comprising the following steps: S1. Dispersing graphitized carbon in an alkaline treatment solution and soaking the solution to obtain a mixture; wherein, during the soaking process, heating or stirring may be selected as required to ensure that the graphitized carbon and the alkaline treatment solution are fully mixed.
[0032] S2. Dry the mixture, heat treat it in an argon atmosphere, and obtain alkali-treated graphitized carbon after washing; wherein the alkali coated on the surface of the graphitized carbon after drying reacts with the carbon under heat treatment, so that the graphitized carbon with fewer defects on the surface is defective, and the specific surface area of the graphitized carbon is increased.
[0033] S3. Impregnating a platinum-based metal catalyst on the alkali-treated graphitized carbon to obtain a platinum-based metal catalyst supported on the alkali-treated graphitized carbon.
[0034] In the present application, graphitized carbon is subjected to alkali treatment, and the carbon on the surface of the graphitized carbon reacts with the alkali to produce more defect sites, which can be used as a platinum-based catalyst carrier for hydrogen fuel cells. The platinum or platinum alloy particles are well dispersed on the alkali-treated graphitized carbon carrier, and the particle size is about 1-10 nm, which is relatively uniform and moderate, which is conducive to ensuring the better performance and stability of the platinum-based catalyst.
[0035] Wherein, the alkaline treatment solution is a mixed solution of alkaline solution and anhydrous ethanol.
[0036] Further, in step S1, the concentration of the alkaline solution is 0.5-10 mol / L, and the alkali in the alkaline solution is one of calcium hydroxide, magnesium hydroxide, rubidium hydroxide, cesium hydroxide, lithium hydroxide, and potassium hydroxide. The selected alkaline treatment solution can increase the surface defect sites, and the metal ions therein can also be embedded in the graphitized carbon material. Among them, when it is not necessary to achieve the relevant intercalation effect, the alkaline solution can also use other corrosive alkalis such as beryllium hydroxide, barium hydroxide, strontium hydroxide, etc.
[0037] Preferably, the alkali in the alkaline solution is potassium hydroxide. In the present application, the alkaline solution of potassium hydroxide has a stronger activation effect on graphitized carbon, and after treatment, potassium ions have the ability to embed into the graphitized carbon material with an ordered organizational structure at a subsequent high temperature, playing an intercalation role, and potassium hydroxide has a stronger activation effect on graphitized carbon. Specifically, when potassium hydroxide reacts with graphitized carbon, K ions are embedded into the graphitized carbon interlayer on the surface of the reducing carbon surface, expanding the graphitized carbon interlayer spacing on the surface, and combining with OH - The corrosion of the radical destroys the carbon-carbon bonds on the carbon surface, thereby increasing the defect sites of the surface carbon, which enables it to better combine with metal nanoparticles. The interlayer spacing of graphitized carbon treated with potassium hydroxide is larger than the theoretical interlayer spacing of ordinary graphite. Since it is difficult for Na ions to embed into the graphite interlayer, the interlayer spacing of graphitized carbon treated with sodium hydroxide is almost unaffected.
[0038] The present application realizes intercalation modification by subjecting graphitized carbon to alkali treatment, and can prepare graphitized carbon with relatively abundant defects, which is beneficial to improving the anchoring effect on platinum-based particles. Agglomeration is not easy to occur during impregnation loading, and the prepared platinum-based metal catalyst also has high performance and stability.
[0039] Furthermore, in step S1, the ratio of graphitized carbon to the alkaline treatment liquid is 1:1-1000 (g / ml). In the present application, the ratio of graphitized carbon to the alkaline treatment liquid can ensure that the graphitized carbon is dispersed and infiltrated in the alkaline treatment liquid, and there is no mandatory requirement for the mixing ratio between them. After infiltration and drying, alkali will remain on the graphitized carbon, which will subsequently corrode and increase surface defects. Specifically, adjusting the concentration and mixing ratio of the alkaline treatment liquid can control the amount of contact between the alkali and the graphitized carbon surface after drying, thereby affecting the degree of alkali treatment.
[0040] Furthermore, in the alkali treatment solution of step S1, the volume ratio of the alkaline solution to anhydrous ethanol is not higher than 50:1. The surface hydrophilicity and hydrophobicity of some graphitized carbon materials are different after preparation. Since some graphitized carbons are highly hydrophobic, they cannot be wetted in aqueous solutions, and the surface cannot be evenly mixed with alkali. The present application contributes to the wetting of graphitized carbon in alkaline solutions by adding anhydrous ethanol. Among them, excessive use of anhydrous ethanol will reduce the concentration of alkali solution, resulting in poor alkali activation effect of graphitized carbon and reduced porosity of alkali-treated graphitized carbon. Generally, only a little is used for wetting. If the graphitized carbon has good hydrophilicity, there is no need to add anhydrous ethanol. Among them, anhydrous ethanol can also use a variety of other organic solvents that are miscible with water.
[0041] Further, in step S2, drying can be performed by evaporation or filtration, preferably by filtration, removing excess alkali treatment solution by filtration, vacuuming and drying the mixture of alkali treatment solution and graphitized carbon, so that the alkali is evenly distributed on the graphitized carbon and coated on the surface, and then drying to remove moisture before subsequent heat treatment.
[0042] Further, in step S2, the temperature of the heat treatment under argon atmosphere is 200-1800°C, and the treatment time is 0.1h-10h. In the present application, heat treatment is a key step, which determines the number of defects on the carbon surface. The corrosion and modification of the graphitized carbon surface are carried out during the heat treatment process, and after high-temperature alkali activation, a richer pore structure can be obtained. If the heat treatment temperature is too high and the alkali activation is excessive, it will cause excessive corrosion to the carbon material; if the heat treatment temperature is too low, the alkali activation effect is poor, and a scarce pore structure is obtained.
[0043] Further, the preparation steps of graphitized carbon include: The amorphous carbon material is kept at 1200-3000° C. for 75 minutes and then naturally cooled to room temperature to obtain graphitized carbon.
[0044] The heat preservation process can be carried out in an inert atmosphere or a reducing atmosphere.
[0045] Preferably, the holding temperature is more preferably 1800° C. Among them, the graphitization degree of holding at 1800° C. for 75 minutes is similar to that of holding at 1500° C. for 5 hours, but the energy consumption of long-term graphitization treatment is higher.
[0046] Specifically, the graphitization degree of graphitized carbon can be controlled by temperature. The higher the temperature, the higher the graphitization degree obtained. The graphitized carbon has a low graphitization degree and is prone to form holes when corroded by alkali. The higher the graphitization degree, the lower the specific surface area, and the alkali treatment effect may not be ideal, which may easily lead to low defect sites. The present application is conducive to obtaining a suitable graphitization degree and ensuring the alkali treatment effect by controlling the treatment at a suitable 1800°C for 75 minutes.
[0047] The amorphous carbon material is carbon with an amorphous structure, and specifically may be one or more of carbon materials with a low degree of graphitization such as Vulcan XC72, KB300, KB600, BP2000, and Toray carbon.
[0048] After the alkali-treated graphitized carbon is obtained through heat treatment, it is washed to remove the residual alkali to avoid affecting the step of impregnating the loaded platinum-based metal catalyst.
[0049] Further, in step S3, the step of impregnating the alkali-treated graphitized carbon with a platinum-based metal catalyst comprises: The alkali-treated graphitized carbon, the precursor solution and water are stirred and mixed uniformly, and treated in a reducing atmosphere at 200-1000° C. for 0.1-10 hours.
[0050] The precursor solution is a platinum precursor solution, or the precursor solution includes a platinum precursor solution and a transition metal precursor solution, and the water used can be ultrapure water. After preparation, a uniformly loaded platinum-based metal catalyst can be obtained on the alkali-treated graphitized carbon.
[0051] Furthermore, the reducing atmosphere can use a hydrogen-argon atmosphere, with the volume proportion of hydrogen being 1-50% (too high will cause explosion risk), preferably 5%, and the remaining argon can also be replaced by various other inert gases. In the present application, hydrogen plays a major reducing role, and with the reducing property of carbon itself, platinum or platinum-based metals will nucleate and grow at the rich defect sites on the surface of alkali-treated graphitized carbon to achieve uniform loading.
[0052] Specifically, the platinum precursor can be one or more of H2PtCl6∙6H2O, K2PtCl6, Na2PtCl6, Na2PtCl4, K2PtCl4, Pt(NH3)4Cl2, Pt(NH3)2(NO2)2, Pt(NO3)2; the transition metal precursor can be one or more of chloroauric acid, cobalt chloride, cobalt nitrate hexahydrate, cobalt sulfate, cobalt acetate, nickel nitrate, ferric chloride, and ferric nitrate. Among them, the amount of platinum precursor can be determined according to the platinum loading, and the loading of the platinum-based metal catalyst can be specifically selected from 10~60% of the commonly used loading (the total loading of all metals on alkali-treated graphitized carbon), and the ratio of platinum to transition metal can be between 1:10 and 10:1.
[0053] The present application proposes to modify the surface of a carbon carrier with a high degree of graphitization, thereby greatly increasing the defect sites and specific surface area of the carbon material while maintaining the graphitized structure, effectively dispersing platinum or platinum-based metal catalysts, and effectively enhancing the dispersion of Nafion ionomers, so that the catalyst has a higher mass specific activity and durability.
[0054] The present application also provides an alkali-treated graphitized carbon-supported platinum-based metal catalyst, wherein the catalyst is prepared by the preparation method of the alkali-treated graphitized carbon-supported platinum-based metal catalyst as described above. In the catalyst provided by the present application, platinum or platinum-based metal is well dispersed on the alkali-treated graphitized carbon carrier, and the particles are small, and the catalyst has good performance and stability.
[0055] The invention is further described below by means of specific examples.
[0056] Example 1 The preparation steps of the graphitized carbon used in Example 1 include: keeping KB600 at 1500° C. for 75 minutes in an inert atmosphere, and naturally cooling it to room temperature.
[0057] The preparation method of the alkali-treated graphitized carbon-supported platinum catalyst of Example 1 comprises the following steps: adding 1.2 g of graphitized carbon to a mixed solution of 30 ml of a KOH solution having a concentration of 5 mol / L and about 1.5 ml of anhydrous ethanol, stirring at room temperature for 1 h to obtain a mixture. The mixture is vacuum dried after suction filtration, and then heat-treated at 600 ° C for 1 h in an argon atmosphere to obtain alkali-treated graphitized carbon. The alkali-treated graphitized carbon is impregnated with platinum, and 1 g of alkali-treated graphitized carbon, about 5.309 g of a hexahydrate chloroplatinic acid solution having a concentration of 33%, and 1 g of ultrapure water are stirred and mixed evenly according to a platinum loading of 40%, and heat-treated at 500 ° C, 5% hydrogen and 95% argon mixed atmosphere for 1 h to obtain the alkali-treated graphitized carbon-supported platinum catalyst of Example 1.
[0058] Comparative Example 1 The preparation method of the graphitized carbon platinum catalyst of Comparative Example 1 is basically the same as that of Example 1, except that the graphitized carbon in Comparative Example 1 is not treated with alkali, but is directly impregnated with platinum to obtain the graphitized carbon-loaded platinum catalyst of Comparative Example 1.
[0059] Electrochemical tests were performed at each stage of the 30,000 cycle stability test. The specific steps were as follows: 5 mg of the prepared catalyst was dispersed in a mixed solution of 5 ml formic acid and 15 μL of 25% Nafion, and ultrasonicated for 1 h to obtain a uniformly dispersed catalyst ink. 10 μL of the catalyst ink was dropped on a 0.196 cm 2 A glassy carbon electrode was used as the working electrode after drying at room temperature, a platinum wire electrode was used as the counter electrode, and a reversible hydrogen electrode was used as the reference electrode to build a three-electrode system.
[0060] The three-electrode system was used for electrochemical testing: at room temperature, O 2 Cyclic voltammetry (CV) and linear sweep voltammetry (LSV) tests were performed in a saturated HClO4 solution (concentration 0.1 mol / L). The scan rate of the linear sweep voltammetry method was 0.02 Vs -1 (0.05-1.00 V). The limiting diffusion current and kinetic current in LSV are used to calculate the mass specific activity (MA) of the catalyst.
[0061] The stability of the three-electrode system was tested by cycling the voltage between 0.60 and 0.95 V vs. RHE for 30,000 times at room temperature in a N2-saturated HClO4 solution (concentration 0.1 mol / L) at 100 mVs -1 The scan rate is performed.
[0062] The ORR results of the electrochemical test of Example 1 and Comparative Example 1 are compared as follows: Figure 1 As shown, the ORR results show that the half-wave potential of the graphitized carbon-supported platinum catalyst in Comparative Example 1 is 0.876 V relative to the reversible hydrogen electrode, and the mass specific activity is only 0.133 A / mg Pt The half-wave potential of the alkali-treated graphitized carbon-supported platinum catalyst of Example 1 is as high as 0.918 V relative to the reversible hydrogen potential, and the mass specific activity is as high as 0.603 A / mg Pt It can be seen that the platinum catalyst supported on the alkali-treated graphitized carbon prepared in Example 1 has higher catalytic performance.
[0063] The ORR result graph and MA comparison graph of the electrochemical test of the alkali-treated graphitized carbon-supported platinum catalyst in Example 1 at each stage of the 30,000-cycle stability test are shown in Figures 1 and 2. Figure 2 and Figure 3As shown, the ORR results show that the alkali-treated graphitized carbon-supported platinum catalyst can stimulate a current of 0.776A at 0.9V, the half-wave potential is as high as 0.918V relative to the reversible hydrogen potential, and the mass specific activity is as high as 0.603A / mg Pt , with excellent initial performance. After 30,000 cycles of stability testing, the half-wave potential of the catalyst was 0.919 V relative to the reversible hydrogen electrode, and the mass specific activity was as high as 0.647 A / mg Pt , the performance is slightly increased, and the prepared catalyst has excellent stability.
[0064] Example 2 The preparation steps of the graphitized carbon used in Example 2 include: keeping KB600 at 1800° C. for 75 min in an argon atmosphere, and naturally cooling it to room temperature.
[0065] The preparation method of the alkali-treated graphitized carbon-supported platinum catalyst of Example 2 comprises the following steps: adding 1.2 g of graphitized carbon to a mixed solution of 30 ml of a KOH solution having a concentration of 5 mol / L and about 1.5 ml of anhydrous ethanol, stirring at room temperature for 1 h to mix evenly to obtain a mixture, and then filtering away most of the ethanol and KOH mixed solution from the mixture. The treated graphitized carbon is vacuum dried and then heat-treated at 600 ° C for 1 h in an argon atmosphere. Impregnation loading platinum, according to 40% platinum loading, 1 g of alkali-treated graphitized carbon, about 5.309 g of hexahydrate chloroplatinic acid with a concentration of 33% and 1 g of ultrapure water are stirred and mixed evenly, and heat-treated at 600 ° C, 5% hydrogen and 95% argon mixed atmosphere for 1 h to obtain the alkali-treated graphitized carbon-supported platinum catalyst of Example 2.
[0066] Comparative Example 2 The preparation method of the graphitized carbon platinum catalyst of Comparative Example 2 is basically the same as that of Example 2, except that the graphitized carbon in Comparative Example 2 is not treated with alkali, but is directly impregnated with platinum to obtain the graphitized carbon-loaded platinum catalyst of Comparative Example 2.
[0067] The XRD comparison patterns of the alkali-treated graphitized carbon obtained in Example 2 and the graphitized carbon obtained in Comparative Example 2 are as follows: Figure 4 As shown in Figure 3, relative to graphitized carbon, the diffraction peak of the (002) crystal plane of alkali-treated graphitized carbon shifts to the left, and the interplanar spacing increases, which may be due to the insertion of K atoms in the graphitized carbon layer.
[0068] The specific surface area test results of the alkali-treated graphitized carbon of Example 2 and the graphitized carbon of Comparative Example 2 are shown in Table 1: Table 1 Group Carbon Materials <![CDATA[SBET(m 2 / g)]]> Comparative Example 2 Graphitized Carbon 384.0379 Example 2 Alkali treated graphitized carbon 458.511 Table 1 shows the difference in specific surface area between the graphitized carbon of Comparative Example 2 and the alkali-treated graphitized carbon of Example 2. After the graphitized carbon is treated with alkali, the specific surface area increases significantly (from 384 m 2 / g increased to 458m 2 / g).
[0069] TEM comparison of the graphitized carbon supported platinum catalyst (a) of Comparative Example 2 and the alkali-treated graphitized carbon supported platinum catalyst (b) of Example 2 is shown in FIG. Figure 5 As shown, since the porosity of the graphitized carbon of Comparative Example 2 is very low and the interaction between the graphitized carbon and the platinum particles is weak, the TEM image shows that the platinum particles on the graphitized carbon are agglomerated and the platinum particles are unevenly dispersed; the alkali-treated graphitized carbon of Example 2 has rich pores and the interaction between the alkali-treated graphitized carbon and the platinum particles is enhanced, which can anchor the platinum particles and prevent the catalyst from agglomerating. In the TEM image, the platinum particles on the alkali-treated graphitized carbon are more evenly dispersed and the catalyst particles are moderate.
[0070] The ORR results of the electrochemical test of Example 2 and Comparative Example 2 are compared as follows: Figure 6 As shown, the ORR results show that the mass specific activity of the graphitized carbon-supported platinum catalyst of Comparative Example 2 relative to the reversible hydrogen potential is only 0.121 A / mg Pt The alkali-treated graphitized carbon-supported platinum catalyst of Example 2 has a mass specific activity of up to 0.536 A / mg relative to the reversible hydrogen potential. Pt , indicating that the alkali-treated graphitized carbon-supported platinum catalyst of Example 2 has higher catalytic performance.
[0071] The ORR result graphs and MA comparison graphs of the electrochemical test of the alkali-treated graphitized carbon-supported platinum catalyst in each stage of the 100,000 cycles stability test of Example 2 are shown in Figures 1 and 2. Figure 7 and Figure 8 As shown, the ORR results show that the alkali-treated graphitized carbon-supported platinum catalyst can stimulate a current of 0.745A at 0.9V, the half-wave potential is as high as 0.914V relative to the reversible hydrogen potential, and the mass specific activity is as high as 0.536A / mg Pt , showing that the catalyst has excellent initial performance. After 100,000 cycles of stability testing, the mass specific activity of the catalyst has not decayed, and the mass specific activity is as high as 0.545A / mg Pt , with remarkably excellent stability.
[0072] Example 2 The TEM images of the alkali-treated graphitized carbon loaded with platinum before and after the stability test are as follows: Fig. 9 As shown in (a) and (b), it can be found that the alkali-treated graphitized carbon-supported platinum catalyst in Example 2 has platinum nanoparticles with a moderate size of about 2-5 nm. After the stability test, the particle size distribution of the catalyst is hardly affected, and the catalyst has significant stability.
[0073] Example 3 The preparation steps of the graphitized carbon used in Example 3 include: keeping Ketjen black at 2000° C. for 75 min and naturally cooling it to room temperature.
[0074] The preparation method of the alkali-treated graphitized carbon-supported platinum catalyst of Example 3 comprises the following steps: 1.2 g of graphitized carbon is added to 30 ml of a mixed solution of a KOH solution having a concentration of 10 mol / L and about 1.5 ml of anhydrous ethanol, stirred at room temperature for 1 h to mix evenly to obtain a mixture, and then the vast majority of the ethanol and KOH mixed solution are filtered off from the mixture. The graphitized carbon after alkali treatment is vacuum dried and then heat-treated at 800°C for 1 h in an argon atmosphere. Impregnation loading of platinum, according to 20% platinum loading, 1 g of alkali-treated graphitized carbon, about 1.991 g of 33% hexahydrate chloroplatinic acid and 0.5 g of ultrapure water are stirred and mixed evenly, and heat-treated at 800°C, 5% hydrogen and 95% argon mixed atmosphere for 1 h to obtain the alkali-treated graphitized carbon-supported platinum catalyst of Example 3.
[0075] Example 4 The preparation steps of the graphitized carbon used in Example 4 include: keeping Ketjen black at 2200° C. for 75 min and naturally cooling it to room temperature.
[0076] The preparation method of the alkali-treated graphitized carbon-supported platinum catalyst of Example 4 comprises the following steps: adding 1.2 g of graphitized carbon to a mixed solution of 30 ml of a KOH solution having a concentration of 10 mol / L and about 1.5 ml of anhydrous ethanol, stirring at room temperature for 1 h to mix evenly to obtain a mixture, and then filtering away most of the ethanol and KOH mixed solution from the mixture. The alkali-treated graphitized carbon is vacuum dried and then heat-treated at 800°C for 1 h in an argon atmosphere. Impregnation loading of platinum, according to 60% platinum loading, 1 g of alkali-treated graphitized carbon, about 11.9475 g of 33% hexahydrate chloroplatinic acid and 1.5 g of ultrapure water are stirred and mixed evenly, and heat-treated at 800°C, 5% hydrogen and 95% argon mixed atmosphere for 1 h to obtain the alkali-treated graphitized carbon-supported platinum catalyst of Example 4.
[0077] Example 5 The preparation steps of the graphitized carbon used in Example 5 are the same as those in Example 1.
[0078] The preparation method of the alkali-treated graphitized carbon-supported platinum-based metal catalyst of Example 5 comprises the following steps: 1.2 g of graphitized carbon is added to 30 ml of a 10 mol / L KOH solution and about 1.5 ml of anhydrous ethanol mixed solution, stirred at room temperature for 1 h to mix evenly to obtain a mixture, and then the vast majority of the ethanol and KOH mixed solution are filtered out from the mixture. The graphitized carbon after alkali treatment is vacuum dried and then heat-treated for 1 h in an argon atmosphere and 800 ° C. Impregnation loading of platinum and cobalt, according to 27% platinum loading and 3% cobalt loading, 1 g of treated graphitized carbon, 2.6236 g of a 33% hexahydrate chloroplatinic acid solution, 2.4574 g of a 20% hexahydrate cobalt nitrate solution and 1 g of ultrapure water are stirred and mixed evenly, and heat-treated for 6 h at 600 ° C, 5% hydrogen and 95% argon mixed atmosphere to obtain the alkali-treated graphitized carbon-supported platinum and cobalt catalyst of Example 5.
[0079] The ORR results of the alkali-treated graphitized carbon supported platinum-cobalt catalyst of Example 5 are as follows: Fig.10 As shown, the 1ORR polarization curve shows that the half-wave potential of the alkali-treated graphitized carbon-supported platinum-cobalt catalyst of Example 5 is as high as 0.932 V relative to the reversible hydrogen potential, and the mass specific activity of the catalyst is as high as 2.126 A / mg Pt , with better catalytic performance.
[0080] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made according to the above description, and all these improvements and changes should fall within the scope of protection of the present application.
Claims
1. A method for preparing an alkali-treated graphitized carbon-supported platinum-based metal catalyst, characterized in that: The following steps are involved: Dispersing graphitized carbon in an alkali treatment solution and soaking it to obtain a mixture; drying the mixture, heat treating it in an argon atmosphere, and washing it to obtain alkali-treated graphitized carbon; The alkali-treated graphitized carbon is impregnated with a platinum-based metal catalyst to obtain the alkali-treated graphitized carbon-supported platinum-based metal catalyst.
2. The method for preparing the alkali-treated graphitized carbon-supported platinum-based metal catalyst according to claim 1, characterized in that: The alkaline treatment solution is a mixed solution of alkaline solution and anhydrous ethanol; The concentration of the alkaline solution is 0.5-10 mol / L, and the alkali in the alkaline solution is one of calcium hydroxide, magnesium hydroxide, rubidium hydroxide, cesium hydroxide, lithium hydroxide, and potassium hydroxide.
3. The method for preparing the alkali-treated graphitized carbon-supported platinum-based metal catalyst according to claim 2, characterized in that: The alkali in the alkaline solution is potassium hydroxide.
4. The method for preparing the alkali-treated graphitized carbon-supported platinum-based metal catalyst according to claim 1, characterized in that: The temperature of the heat treatment in the argon atmosphere is 200-1800° C., and the treatment time is 0.1 h-10 h.
5. The method for preparing the alkali-treated graphitized carbon-supported platinum-based metal catalyst according to claim 2, characterized in that: The ratio of the graphitized carbon to the alkaline treatment liquid is 1:1-1000 (g / ml); The volume ratio of the alkaline solution to anhydrous ethanol is not higher than 50:
1.
6. The method for preparing the alkali-treated graphitized carbon-supported platinum-based metal catalyst according to claim 1, characterized in that: The preparation steps of the graphitized carbon include: The amorphous carbon material is kept at 1200-3000°C for 75 minutes and then naturally cooled to room temperature.
7. The method for preparing the alkali-treated graphitized carbon-supported platinum-based metal catalyst according to claim 6, characterized in that: The amorphous carbon material is one or more of Vulcan XC72, KB300, KB600, BP2000 and Toray carbon.
8. The method for preparing an alkali-treated graphitized carbon-supported platinum-based metal catalyst according to claim 1, characterized in that: The step of impregnating the alkali-treated graphitized carbon with a platinum-based metal catalyst comprises: The alkali-treated graphitized carbon, the precursor solution and water are stirred and mixed, and treated in a reducing atmosphere at 200-1000° C. for 0.1-10 h; The precursor solution is a platinum precursor solution, or the precursor solution includes a platinum precursor solution and a transition metal precursor solution.
9. The method for preparing the alkali-treated graphitized carbon-supported platinum-based metal catalyst according to claim 8, characterized in that: The reducing atmosphere is an argon-hydrogen atmosphere, with the volume proportion of hydrogen being 1-50%; The platinum precursor in the platinum precursor solution is one or more of H2PtCl6∙6H2O, K2PtCl6, Na2PtCl6, Na2PtCl4, K2PtCl4, Pt(NH3)4Cl2, Pt(NH3)2(NO2)2, and Pt(NO3)2; The transition metal precursor in the transition metal precursor solution is one or more of chloroauric acid, cobalt chloride, cobalt nitrate hexahydrate, cobalt sulfate, cobalt acetate, nickel nitrate, ferric chloride, and ferric nitrate.
10. An alkali-treated graphitized carbon-supported platinum-based metal catalyst, characterized in that: The catalyst is prepared by the method for preparing a platinum-based metal catalyst supported on alkali-treated graphitized carbon as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Carbon-supported platinum catalyst powder as well as preparation method and application thereof
CN111509240A
Preparation method of KOH-activated boron and phosphorus-doped graphitized carbon-nitrogen compound positive electrode material
CN111740109A
Method for improving stability of fuel cell carbon-supported platinum-based catalyst through carbon carrier activation
CN114300693A
Preparation method of platinum-based synergistic catalyst with structure coupling effect
CN114497585A
Graphitized carbon loaded platinum nanoparticles, and preparation method and application thereof
CN116111123A